Pengaruh Lembar Kerja Peserta Didik (LKPD) Berbasis Montessori Terhadap Kemampuan Hots (High Order Thinking Skills) Pada Pembelajaran Matematika - Arista Selly Maharani; Sholeh Hidayat; Yoma Hatima (Universitas Hamzanwadi, 2025)
This study aims to analyze the effect of Montessori-based Student Worksheets (LKPD) on HOTS (High Order Thinking Skills) abilities in mathematics learning in grade IV students of SD Negeri Balaraja 03. The research method used is pre-experimental with a One Group Pretest-Posttest Design research design. There is one class in this study, namely the experimental class consisting of 36 students who apply learning using Montessori-based LKPD. The collection of research data uses observation instruments and pretests and posttests. Data analysis is carried out using descriptive statistics and inferential statistics. Inferential data analysis uses the non-parametric Wilcoxon Signed Rank Test. The results achieved were students' HOTS ability before using Montessori-based LKPD, the average class was 52.93 and the standard deviation was 22.65, increased after using Montessori-based LKPD, the average class was 64.32 and the standard deviation was 19.98. HOTS ability using Montessori-based LKPD was better with the results obtained or -1.645> -25.62 <1.645